Anatomy of Africa’s evil Siamese twins: a comparative research of Boko Haram and al-Shabab - Afriyie, Frederick Appiah; Jian, Jisong; Arkorful, Vincent (Penerbit Universiti Kebangsaan Malaysia, 2020)
The activities of terrorist movements like the Boko Haram and the Al-Shabab in recent times have dealt a hefty blow to the collective stability of the African continent and its multi-pronged socio-economic fortunes. The ensuing debacles and the varying inundating levels of ignominy and infamy wreaked on Africa by these groups have spontaneously elicited reactions from the global community over the years. Though steady progress has been made in this regard, the swinging and vacillating strategies of the sect to adopting unconventional mediums to carrying out domestic and transnational attacks leaves much to be desired. Relying on secondary data, this study undertakes a comparative analysis of the Boko Haram and Al-Shabab. Through a review of existing documents, this article argues in line with policy ramifications that, in as much as policy homogeneity may be essential, and perhaps a sine qua non-alternative to be relied on in the quest for the fight against these anti-social incendiary sects, there is still less fruitful outcome and therefore necessitates the need for further policy options. In conclusion, the research equally entreats a neck turn consideration of experimenting with individual countryspecific policy options as a way to fight terrorism, all within a much stronger broader international community framework. Until this is considered, terrorism may remain an albatross around the neck of Africa, and the international community whiles the fight becomes a façade.